2021
DOI: 10.1002/jmrs.526
|View full text |Cite
|
Sign up to set email alerts
|

Improving efficiency in the radiation management of multiple brain metastases using a knowledge‐based planning solution for single‐isocentre volumetric modulated arc therapy (VMAT) technique

Abstract: Introduction: This study aimed to develop a single-isocentre volumetric modulated arc therapy (si-VMAT) technique for multiple brain metastases using knowledge-based planning software, comparing it with a multipleisocentre stereotactic radiosurgery (mi-SRS) planning approach. Methods: Twenty-six si-VMAT plans were created and uploaded into RapidPlan TM (RP) to create a si-VMAT model. Ten patients, with 2 to 6 metastases (mets), were planned with a si-VMAT technique utilising RP, and a mi-SRS technique on Brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Nevertheless, it is worth mentioning that a randomized phase III study by Belderbos et al (2019) did not find any difference in patients' memory compared to the standard PCI [17][18][19]. The VMAT technique for whole-cranial irradiation may protect the hippocampus by delivering a lower than the prescribed radiation dose to that organ in order to reduce toxicity, but with a higher number of MUs than a three-dimensional conformal radiation therapy (3DCRT) of whole-cranial and less than intensity-modulated radiation therapy (IMRT) [20,21]. Such a treatment plan is a challenge in clinical practice for the radiation therapy department since the thresholds for the hippocampus are pretty low and its volume is small compared to the volume of the whole brain.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is worth mentioning that a randomized phase III study by Belderbos et al (2019) did not find any difference in patients' memory compared to the standard PCI [17][18][19]. The VMAT technique for whole-cranial irradiation may protect the hippocampus by delivering a lower than the prescribed radiation dose to that organ in order to reduce toxicity, but with a higher number of MUs than a three-dimensional conformal radiation therapy (3DCRT) of whole-cranial and less than intensity-modulated radiation therapy (IMRT) [20,21]. Such a treatment plan is a challenge in clinical practice for the radiation therapy department since the thresholds for the hippocampus are pretty low and its volume is small compared to the volume of the whole brain.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in their multiple isocentre technique, each metastasis requires its own plan and treatment delivery. 40 Where quality improvements in studies are reported, it is not necessarily the case that KBP planning performs better in every metric. In some cases, improved performance in one area might be offset by a reduction in another.…”
Section: Srsmentioning
confidence: 99%
“…For example, O'Toole et al found that the average CI were better in KBP plans but that low-dose wash was worse in four out of five dose levels. 40 Like all radiotherapy planning, there are trade-offs in what can be prioritised; therefore, studies that include blinded physician review are of particular interest, as discussed earlier.…”
Section: Srsmentioning
confidence: 99%